Clinical Characteristics of Multisystem Inflammatory Syndrome in Children and Young Adults With COVID-19: A Rapid Systematic Review - Manish Kumar; Swarnim Swarnim; Pallavi Pallavi (Mazandaran University of Medical Sciences, 2022)
Background: The associated multisystem inflammatory syndrome in children (MIS-C) with coronavirus disease (COVID-19) is a novel syndrome that has phenotypic similarity to Kawasaki disease (KD).  Objectives: This study systematically reviewed the demographic profile, clinical spectrum, treatment options, and outcomes of children and young adults under 21 years of age suffering from MIS-C.  Methods: PubMed and Embase databases were searched from inception to July 3, 2020. A total of 39 studies involving 799 participants were included in the review. Critical appraisal of included studies was done using Joanna Briggs Institute Critical Appraisal Checklist for studies reporting prevalence data. A narrative synthesis was performed through descriptive summaries of demographic variables, clinical features, investigations, treatment details, and clinical outcomes. Results: The main complaints of the patients were fever (96.4%) followed by gastrointestinal symptoms. Serological evidence of preceding severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection was documented in 79.1% of the participants. Ventricular dysfunction (50.2%) was the most common echocardiographic finding. Intensive care was required for 77% of included participants, with 27.2% being mechanically ventilated. Also, 78.1% of the participants received intravenous immunoglobulins. The overall mortality rate was 1.5%. Conclusions: MIS-C associated with COVID-19 clinically resembles a hyperinflammatory state. More extensive studies will help in better defining this entity and delineating its phenotypic subtypes.